Fault Detection Experiment of Unbalanced Voltage and Air Gap Eccentricity on Induction Motor Using a Flux Sensor - Husnah, Nurul; Asfani, Dimas Anton; Negara, I Made Yulistya (Department of Electrical Engineering ITS and FORTEI, 2023)
Abstract— The induction motor is one of the popular equipment used in various types of industrial sectors. It is necessary to monitor the condition of the induction motor to maintain its safety and performance of the induction motor. The most common damage to the induction motor is bearing failure reaches 40% resulting in air gap eccentricity. Most of the research to detect the occurrence of air gap eccentricity is carried out based on the analysis of motor current signals. To overcome the disadvantages of the above methods, the detection of air gap eccentricity using a sensor flux that can detect leakage flux from the motor body and the fault detection results by measuring the flux signal analyzed. Flux analysis using the Fast Fourier Transform (FFT) algorithm in balanced and unbalanced voltage conditions. Induction motor failure analysis compared normal motor conditions with an eccentricity of 0.1 mm and 0.2 mm. Eccentricity detection is done by monitoring the amplitude that emerges in the frequency spectrum with notice of the threshold. Detection results from the eccentricity fault showed that success is detected 100% using a sensor flux on unbalanced voltage (under voltage 5%) at a full-load condition.